Pelatihan Kewirausahaan Pembuatan dan Promosi Digital Marketing Batik Jenggolo - Jajuk Herawati; Lusia Tria Hatmanti Hutami; Pristin Prima Sari (ABDIMAS DEWANTARA, 2019)
Community service activity is related to Training of Entrepreneurship Making and Promotion Digital Marketing Batik To Women Fostering Family Welfare (PKK). The purpose of this activity is to introduce entrepreneurship and digital marketing of handmade batik to the women PKK Pandeyan Numbers. In addition, PKK women can follow up to have store of batik from their production. The venue is located at RW 04 Pandeyan Hall. The activity targets are women PKK Kalangan Pandeyan. The implementation followed by cooperation with Sanggar Batik Jenggolo as a speech how to make batik. Training methods are studying, discussions and practices. Training activities include entrepreneurship, promotion, product decisions and branding, digital marketing and making batik. The result of this activity is handkerchief batik.Keyword: Entrepreneurship, Digital Marketing, Batik Tulis